Clinical, Laboratory, and Molecular Characteristics and Remission Status in Children With Severe Congenital and Non-congenital Neutropenia - Gong, Ruo-Lan; Wu, Jing; Chen, Tong-Xin (Frontiers in Pediatrics, 2018)
Objectives: Severe congenital neutropenia (SCN) is a primary immunodeficiency disease characterized by the early onset of recurrent infections and persistent severe neutropenia, with or without genetic defect. We aimed to study the different clinical features and haematological and bone marrow characteristics of patients with SCN and the non-congenital form of severe neutropenia (SN) with unknown aetiology. Methods: Thirty-nine Chinese children with severe neutropenia for longer than 6 months unrelated to virus infection or autoimmune diseases were enrolled in the study to analyse the clinical, laboratory and molecular characteristics. They were followed clinically to observe their remission status. Results: Seven patients were found to have SCN mutations, including ELANE and G6PC3. Among 26 patients with close follow-up, one died for an unknown reason, and 10 resolved spontaneously with a median neutropenia duration of 14.5 months; these patients were designated as having recovered SN. The demographic characteristics of both groups were similar, with a median infection rate of 5 times/year. SCN patients had more frequent infection than recovered SN patients (4 times/year, P=0.039). The median absolute neutrophil count (ANC) was 0.40×109/L in SCN patients, which was significantly higher than 0.2×109/L in SN with unknown aetiology and 0.21×109/L in recovered SN patients (P=0.021, P=0.017). The median monocyte count was 1.60×109/L in SCN patients, which was also significantly higher than 0.57×109/L in SN of unknown aetiology and 0.55×109/L in recovered SN patients (P=0.018, P=0.001). Bone marrow examinations demonstrated myeloid maturation arrest at the myelocyte-metamyelocyte stage in SCN patients and normal findings in SN with unknown aetiology and recovered SN patients. Conclusions: Patients with severe neutropenia due to gene mutations demonstrate more serious symptoms than patients with unknown aetiology. Patients with relatively higher ANC and monocyte counts are more likely to have known gene mutations. Future studies should focus on more detailed laboratory investigation, prolonged follow-up and advanced molecular biology tools to facilitate accurate diagnosis and effective treatment.